2000
DOI: 10.1073/pnas.97.21.11598
|View full text |Cite
|
Sign up to set email alerts
|

Sensory neuron-specific sodium channel SNS is abnormally expressed in the brains of mice with experimental allergic encephalomyelitis and humans with multiple sclerosis

Abstract: Clinical abnormalities in multiple sclerosis (MS) have classically been considered to be caused by demyelination and͞or axonal degeneration; the possibility of molecular changes in neurons, such as the deployment of abnormal repertoires of ion channels that would alter neuronal electrogenic properties, has not been considered. Sensory Neuron-Specific sodium channel SNS displays a depolarized voltage dependence, slower activation and inactivation kinetics, and more rapid recovery from inactivation than classica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 117 publications
(61 citation statements)
references
References 45 publications
(55 reference statements)
2
57
0
2
Order By: Relevance
“…Although cerebellar neurons express TTX-sensitive VGSCs, TTX-resistant (TTX-R) Na v 1.8 is up-regulated under pathophysiological conditions (40)(41)(42). TTX-R Na v 1.5 channels also are upregulated in Scn1b null ventricular myocytes (12).…”
Section: Resultsmentioning
confidence: 99%
“…Although cerebellar neurons express TTX-sensitive VGSCs, TTX-resistant (TTX-R) Na v 1.8 is up-regulated under pathophysiological conditions (40)(41)(42). TTX-R Na v 1.5 channels also are upregulated in Scn1b null ventricular myocytes (12).…”
Section: Resultsmentioning
confidence: 99%
“…In post-mortem analysis of human cerebellar Purkinje cells from multiple sclerosis patients, Na v 1.8 mRNA and protein levels were up-regulated, presumably being related to cerebellar ataxia seen in multiple sclerosis patients (37,48).…”
Section: Sodium Channel Remodeling In Neurodegeneration: Demyelinatiomentioning
confidence: 99%
“…It has been shown that Na V 1.8 channels are expressed ectopically in the cerebellar Purkinje neurons of patients with MS and mice with experimental autoimmune encephalomyelitis (EAE). 6,7 This channelopathy causes abnormal firing patterns in the cerebellar Purkinje cells 8,9 and motor coordination deficits in the absence of obvious signs of ataxia in mice models. 5 In this study, we aimed to examine the effects of potentially functional SCN10A genetic variations on clinical and imaging outcomes in patients with MS. We hypothesized that consistent with results from animal studies SCN10A genotype would affect performance in motor coordination tasks in MS, irrespective of gross clinical ataxia.…”
Section: ) Patients With Ms With Rs6795970mentioning
confidence: 99%